SCREENING POLE OF GREEN FOREST CHICKEN (Gallus varius) AND ITS POTENTIAL AS A TEACHING SOURCE OF BIOCULTURAL DIVERSITY: A CASE STUDY IN BUKIT DEMULIH BANGLI INDIGENOUS FOREST AREA - Sang Putu Kaler Surata (Journal of Natural Sciences and Learning, 2023)
Green jungle fowl (Gallus varius) is widespread in nature and community forests. This study aims to identify distribution patterns, habitat profiles, and the potential of green jungle fowl (GJF) as a source of biological learning based on a biocultural approach (biodiversity, cultural diversity, and language diversity). The case study was used for extensive bird exploration in a customary forest, Hutan Adat Bukit Demulih Bangli (HABD), from February to June 2022. Data on distribution patterns were collected with a combination of free-range, line transect, and point-count techniques and habitat profiles with physiognomy methodology. Meanwhile, document analysis and the concept map were used to demonstrate the potential of the GJF in HABD as a source of learning. The results revealed that GJF was unequally distributed, with a population at each observation point ranging from 2 to 10. The bird prefers forested areas dominated by shrubs with several trees and, therefore, has an open canopy that allows sunlight to reach the forested floor. Local knowledge and practices in the preservation of GJF and HABD are excellent resources for learning various biological materials and concepts in the context of biodiversity, culture, and language.